Модифицированная роторно-турбинная насадка для создания водяной завесы - Kotov Геннадий; Golub Олег (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2012)
The article is devoted to the development of modified rotary-turbine casing head provided with replaceable impeller and changeable diameter of nozzles. The results of verification nature test to determine technical characteristics of the casing head and parameters of created water curtain are presented.